2011
DOI: 10.1007/s00248-011-9842-7
|View full text |Cite
|
Sign up to set email alerts
|

Culturable Diversity of Heterotrophic Bacteria in Forlidas Pond (Pensacola Mountains) and Lundström Lake (Shackleton Range), Antarctica

Abstract: Cultivation techniques were used to study the heterotrophic bacterial diversity in two microbial mat samples originating from the littoral zone of two continental Antarctic lakes (Forlidas Pond and Lundström Lake) in the Dufek Massif (within the Pensacola Mountains group of the Transantarctic Mountains) and Shackleton Range, respectively. Nearly 800 isolates were picked after incubation on several growth media at different temperatures. They were grouped using a whole-genome fingerprinting technique, repetitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 62 publications
2
53
0
Order By: Relevance
“…The absence of hydrological features (ponds and lakes) in the Beacon Valley compared to Miers Valley was considered an important factor in explaining the differences in cyanobacterial compositions between the two valleys (Wood et al 2008). Heterotrophic bacteria in microbial mats, which include representatives of the phyla Actinobacteria, Proteobacteria, Bacteroidetes, Firmicutes, and Deinococcus-Thermus (Brambilla et al 2001;Van Trappen et al 2002;Rojas et al 2009;Peeters et al 2011), may be similarly redistributed by aeolian processes in Antarctic ecosystems. Indeed, proximity to hydrological features was found to be more important than soil moisture for describing variation in both bacterial and cyanobacterial community structures in Miers Valley soils (Niederberger et al 2012).…”
Section: Desert Soilsmentioning
confidence: 99%
“…The absence of hydrological features (ponds and lakes) in the Beacon Valley compared to Miers Valley was considered an important factor in explaining the differences in cyanobacterial compositions between the two valleys (Wood et al 2008). Heterotrophic bacteria in microbial mats, which include representatives of the phyla Actinobacteria, Proteobacteria, Bacteroidetes, Firmicutes, and Deinococcus-Thermus (Brambilla et al 2001;Van Trappen et al 2002;Rojas et al 2009;Peeters et al 2011), may be similarly redistributed by aeolian processes in Antarctic ecosystems. Indeed, proximity to hydrological features was found to be more important than soil moisture for describing variation in both bacterial and cyanobacterial community structures in Miers Valley soils (Niederberger et al 2012).…”
Section: Desert Soilsmentioning
confidence: 99%
“…Two new strainlevel Marinobacter sp. cultivars closely related to strains isolated from other Antarctic lake systems (56,60) (Table 1) were isolated in this study, though no Marinobacter isolates were detected in the Յ0.2-m brine fraction. Three Psychrobacter isolates (closely related to LV414) (32) and one Gram-positive Arthrobacter-related isolate (strain LV10R520-3) were also identified among the unfiltered brine cultures.…”
Section: Discussionmentioning
confidence: 97%
“…In all cases, we isolated organisms that were closely related (Ͼ97% sequence identity) to organisms from cold habitats but did not have identical 16S rRNA gene sequences to previously isolated strains. Micrococcaceae (strain LV10fR510-15), which represented the majority of the 0.2-m-brine-fraction isolates, were closely related (98.8% identity) to Microbacterium lacus strain R-43968 isolated from a microbial mat at Lundström Lake, West Antarctica (56). Relatives of other 0.1-to 0.2-m-brinefraction strains (strain LV10fR510-14 and LV10fR520-8) were derived from northern high-latitude ecosystems in or near Siberia ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [3,[25][26][27][28][29] have shown that there is a very high density of new or unknown actinomycetes in Antarctic environments. In our phylogenetic analysis, cultures were obtained from a wide range of existing genera that are mostly cosmopolitan.…”
Section: Resultsmentioning
confidence: 99%